Traditional Musical Instruments of the Tolaki People - Untung untung; Tambunan Tambunan; Saasa Saasa; Mariyatul Kiptiyah; Darmin (Journal of Law, Social Science and Management, 2025)
Background: Traditional music constitutes an essential element of cultural identity, including that of the Tolaki ethnic group in Southeast Sulawesi. However, with the progression of time and the growing influence of globalization, the presence and recognition of traditional musical instruments have gradually diminished, particularly among younger generations.Objectives: This study aims to explore the diversity of traditional musical instruments of the Tolaki people, the techniques involved in their use, and the cultural values embedded within them.Methods: A qualitative descriptive method with an ethnographic approach was employed, involving direct observation, in-depth interviews with cultural elders, and an extensive review of related literature.Results: The findings indicate that traditional musical instruments such as karandu, lado-lado, dimba-dimba nggowuna, ore-ore nggae, kanda-kanda wuta, kanda-kanda oa, gambusu, wuwuho, and dimba serve not only as mediums of artistic expression but also hold vital roles in traditional ceremonies, agricultural rituals, and the reinforcement of cultural identity. Each instrument possesses distinct characteristics in terms of material composition, playing techniques, and its sociocultural function.Conclusion: The study underscores the urgency of preserving and revitalizing the traditional musical instruments of the Tolaki tribe as a valuable component of Indonesia’s intangible cultural heritage. Efforts toward revitalization should include the integration of local cultural education, systematic documentation, and the organization of regular traditional music performances.